1991
DOI: 10.1254/jjp.55.513
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Sensitivity of .ALPHA.1-Adrenoceptor Stimulants and .ALPHA.1-Adrenoceptor Mechanisms in Rabbit Arteries.

Abstract: Sensitivity (pD2 value, negative logarithm of the molar concentration producing the half maximum response) and affinity (pKA value, negative logarithm of dissociation constant) of norepinephrine were determined in 6 arteries from rabbits. A positive correlation was found in the pD2 and pKA values of norepinephrine. The slope was not significantly different from 1. The pD2 and pKP (a negative logarithm of dissociation constant of a partial agonist) values of tizanidine, an a,-partial agonist, were also determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These characteristics may be modified by aging (3,4) or the development of diseases such as hypertension, diabetes or arteriosclerosis (5,6,7). Accordingly, studies of the contractile effects of norepinephrine in arteries from rabbits (8) as well as in both arteries and veins from canines (9,10) demonstrated that alpha 1 -adrenoceptor-mediated arterial and vein sensitivity varied by species and region. Quantitative and qualitative regional variations in the alpha 1 -adrenergic vasocontractile effects may be due to differences in the number, affinity or subtype of alpha 1 -adrenergic receptors, as well as differences in the predominant intracellular pathways of distinct vascular regions (11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics may be modified by aging (3,4) or the development of diseases such as hypertension, diabetes or arteriosclerosis (5,6,7). Accordingly, studies of the contractile effects of norepinephrine in arteries from rabbits (8) as well as in both arteries and veins from canines (9,10) demonstrated that alpha 1 -adrenoceptor-mediated arterial and vein sensitivity varied by species and region. Quantitative and qualitative regional variations in the alpha 1 -adrenergic vasocontractile effects may be due to differences in the number, affinity or subtype of alpha 1 -adrenergic receptors, as well as differences in the predominant intracellular pathways of distinct vascular regions (11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The [3H]prazosin binding assay was performed using mem brane preparations in 50 mM Tris-HCI, according to the method used by Takayanagi et al (7). The membrane preparations (150,ug protein/tube) were incubated with 0.2 nM [3H]prazosin in the presence or absence of 10 ,u M GTP y-S in 50 mM Tris-HC1 buffer for 30 min at 32°C.…”
mentioning
confidence: 99%